P40 Cross-specialty collaboration in the development of a national survey of practice for emergency scrotal exploration. (8th April 2021) - Boam, Tristan; Harwood, Rachel; Clement, Keiran; Light, Alexander; Kasivisvanathan, Veeru; Hotonu, Sesi; Marks, Isobel; Boam, Tristan
Abstract: Introduction: Emergency scrotal exploration for suspected testicular torsion is a common procedure, performed by Paediatric surgeons, Urologists and General Surgeons. It is expected that there is variation in practice in the way that testes are fixed after torsion and other pathologies, both within departments and across specialties. We aim to survey UK practice, and describe the impact of patient age, surgical specialty and grade of surgeon for this procedure. Methods: The Paediatric Surgery Trainee Research Network (PSTRN) and the British Urology Researchers in Surgical Training (BURST) groups are developing an electronic national survey of practice. This will be distributed to every UK hospital; Paediatric, General and Urology Surgeons of Consultant and Middle Grade will be asked to participate if they offer this procedure as part of their current practice. Results: After a discussion of some initial survey drafts, the PSTRN-BURST collaboration met over teleconference. The scope of the questions were broadened from looking only at fixation methods to include the initial surgical approach, methods of skin closure and a comparison between paediatric and adult practice and how the procedure changes based on the stage of puberty. The questions were refined and made more granular, and to facilitate this, the platform was changed from Google forms®, to REDCap® and finally, to Microsoft Forms®. Conclusions: As a result of inter-specialty collaborative working, the quality of the survey questions has greatly improved. The survey is now structured in a manner that will yield the most scientifically valid conclusions and aims to benefit all clinicians that undertake emergency scrotal exploration.